Podocytes are likely the therapeutic target of IgA nephropathy with isolated hematuria: Evidence from repeat renal biopsy - Luo, Mian-Na; Yin, Yanqing; Li, Shangmei; Hao, Junfeng; Yao, Cuiwei; Xu, Yong-Zhi; Liu, Hua-feng; Yang, Lawei (Frontiers in Pharmacology, 2023)
Background: The present study aimed to prove the progression of immunoglobulin A nephropathy (IgAN) patients with isolated hematuria based on repeat renal biopsy data for the first time. Methods: 29 IgAN patients with isolated hematuria who received repeat renal biopsies were analyzed retrospectively, while 29 non-isolated hematuria IgAN patients with similar age and background were randomly selected as the control group. Clinical parameters were collected at the time of biopsy. The treatment strategies (conservative treatment with RASS blocker or immunosuppressive treatment) were choosen according to the pathological results at the first renal biopsy. The activity and chronicity indexes of renal lesions were evaluated. Markers of cell inflammation and proliferation were tseted by immunochemistry. The ultrastructure of podocytes was observed by transmission electron microscopy (TEM). Podocyte and oxidative stress marker (NPHS2 and 4-HNE) were detected by immunofluorescence. Results: The IgAN patients with isolated hematuria had better clinical indicators than those with no-isolated hematuria, such as better renal function, higher albumin and lower uric acid. The interval between two biopsies in IgAN patients with isolated hematuria was 630 (interquartile range, 409.5–1,171) days. The hematuria of the patients decreased significantly from 30 (IQR, 4.00–35.00) RBC/ul in the first biopsy to 11 (IQR, 2.50–30.00) RBC/ul in the repeated biopsy (p < 0.05). The level of triglyceride decreased significantly (p < 0.05). The other clinical indicators were not statistically significant (p > 0.05). Deposits of IgA and C3 in the glomerulus were persistent. The activity index decreased, especially cellular crescent formation, while the chronicity index increased. The ultrastructure of podocytes was improved after treatment. The oxidative stress products of podocytes reduced after treatment. Conclusion: Although the clinical indicators of the IgAN patients with isolated hematuria were in the normal range, various acute and chronic pathological changes have occurred, and irreversible chronic changes have been progressing. Cell inflammation and proliferation persisted. Oxidative stress of podocytes was likely to be the therapeutic target. This study provided a strong basis for the progress of IgAN with isolated hematuria through pathological changes before and after treatment. This study will help clinicians recognize the harm of hematuria, change the traditional treatment concept, and help such patients get early treatment.